2013
DOI: 10.1111/nhs.12035
|View full text |Cite
|
Sign up to set email alerts
|

After theDoctorate: A qualitative study investigating nursing research career development inJordan

Abstract: There is a dearth of research exploring the development of postdoctoral nursing research careers in non-Western contexts. This paper reports on a qualitative study of Jordanian graduates of UK PhD programs. Interviews were held with 16 graduates who worked in the nursing faculty of seven different universities in Jordan. Participants reported that their doctoral degree had equipped them with confidence and enthusiasm for developing a research career. Mentorship, leadership, and peer support were identified as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 24 publications
4
40
0
Order By: Relevance
“…Other push and pull factors included the desire to travel and career advancement, which echo the results of other studies of Jordanian nurses and students (3,7). This is similar to studies which suggested that nursing is seen as a mobile profession with work opportunities tied to travel (2,6,16,17). It is likely that the similarities in language, culture and religious beliefs between Jordan and the GCC countries are key factors in pulling the nurses.…”
Section: Discussionsupporting
confidence: 64%
“…Other push and pull factors included the desire to travel and career advancement, which echo the results of other studies of Jordanian nurses and students (3,7). This is similar to studies which suggested that nursing is seen as a mobile profession with work opportunities tied to travel (2,6,16,17). It is likely that the similarities in language, culture and religious beliefs between Jordan and the GCC countries are key factors in pulling the nurses.…”
Section: Discussionsupporting
confidence: 64%
“…For Jordanian nurses who completed doctorates in the UK and then returned home, leadership in nursing research was absent due to absence of researchers and only 56% ( n = 16) sustained their research despite high self‐confidence (Al‐Nawafleh et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…This is a reflection of the current level of the research culture in nursing. Without a fostering research culture, almost half the nurses who have PhDs stop doing research (Al‐Nawafleh, Zeilani, & Evans, ). This implies a significant leakage of academic knowledge and skills that are needed to provide high‐quality patient care, and this waste of talent is costly (Buchan, ; O'Brien‐Pallas, Murphy, Shamian, Li, & Hayes, ).…”
Section: Discussionmentioning
confidence: 99%